Detection of Visceral leishmaniosis by RT-PCR technique in Wasit Province of Iraq. - Zahraa Ali Faieq (Journal of Wasit for Science and Medicine, 2023)
The current study was conducted in an advisory Pediatric in Al Zahra Hospital and Al-Karamah Teaching Hospitals in the city of Kut. This study included determining the extent of Kala-azar disease in the Wasit Province using Real-time PCR reaction in the present study. We collected 70 samples of suspected cases infected by visceral leishmaniasis. The results were 50/70 [71%] were positive and 20/70 [29%] negative in real-time PCR reaction test. The most age that have ability to infect with donovani was under one year.